Percepción de los niveles personal, familiar, educativo, social y afectivo en internos de la penitenciaria de Acacias, Meta (2017)
In this article presents the results of research based on understanding This study aimed to identify, identify and describe the perception of the inmates of Hall 4 of the Acacias-Meta penitentiary on personal, family, educational, social and affective levels according to the ecological model.To begin with, the theory of the ecological model postulated by Brofenbrenner (1987) consists in the scientific study of the progressive mutual accommodation between an active human being in development and the changing properties of the immediate environments in which the person lives (systems) (p .40), which is the "interrelationship of different elements, whether objects, situations or elements, processes, variables, in an organized way which always have a certain function" (p.7).In this way, the situation of incarceration is an experience difficult to assimilate for the person deprived of liberty and their families, at least in the first moments of prison, which generates in these people a constant adaptive effort that, as a consequence , Generates a series of affective, emotional, cognitive and perceptive distortions (Altimirano, 2013), since there are restrictions such as emotional isolation and frustration (Arroyo, 2011); There are also factors that impact on the individual, and which are associated with the same condition of internment, such as deprivation of freedom, withdrawal from social and family networks, withdrawal from working life, cognitive stress associated with concerns By family situation, overcrowding, lack of privacy, among others (Ruiz, 1999).It has as a general objective To know the perception of the inmates of Hall 4 of the penitentiary of Acacias-Meta on the levels of the systems of the ecological model (family, educational, social and affective).As for the methodology was a qualitative approach, phenomenological design, a sample of 22 inmates of ward 4 between the ages of 19 to 44 years; For data collection an in-depth interview was applied. Finally, the analysis of information was carried out through the Atlas Ti program, which is a flexible tool that allows analyzing several aspects and therefore greatly facilitates the organization, management and interpretation of qualitative data (Cuevas and Méndez, 2012).